1992
DOI: 10.1111/j.2042-7158.1992.tb05483.x
|View full text |Cite
|
Sign up to set email alerts
|

Amorphism and Physicochemical Stability of Spray-dried Frusemide

Abstract: The physicochemical properties of amorphous forms of frusemide, prepared by spray-drying at 50 or 150 degrees C, and their hygroscopic stability at temperatures of 25 and 40 degrees C, and at 0 and 75% relative humidity were investigated. The glass transition temperature of the amorphous form A was 44.2 degrees C as measured by differential scanning calorimetry, while that of the amorphous form B was 54.4 degrees C. The activation energies for glass transition and crystallization processes were calculated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 9 publications
(11 reference statements)
2
14
0
Order By: Relevance
“…11,12 The moisture sorption/desorption isotherms of the spray-dried and freeze-dried lamotrigine mesylate were essentially identical. The critical moisture content of spray-dried lamotrigine mesylate was 7.6% (SD ) 0.06, n ) 3) at 70-75% RH.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 The moisture sorption/desorption isotherms of the spray-dried and freeze-dried lamotrigine mesylate were essentially identical. The critical moisture content of spray-dried lamotrigine mesylate was 7.6% (SD ) 0.06, n ) 3) at 70-75% RH.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] As a result of this, the temperature dependence of molecular motions below the glass transition temperature is highly dependent upon the conditions under which the glass was formed. 12 This temperature dependence is generally less extreme than above T g and more linear, with some authors proposing an Arrhenius-like relationship.…”
Section: Definition and Description Of The Amorphous Statementioning
confidence: 98%
“…Interestingly, Corrigan (1995) has described how changing the spray drying conditions may result in the formation of materials with differing T g values and physical properties. For example, Matsuda et al (1992) prepared amorphous frusemide using two spray drying protocols and reported that the resultant materials had differing T g values (44.2 and 54.4°C). These changes may be a result of differences in moisture content but the study clearly demonstrates the dependence of T g on spray drying protocol.…”
Section: The Physical Stability Of Amorphous Drugsmentioning
confidence: 99%